METACOGNITIVE MONITORING ACCURACY AND LEARNING ACHIEVEMENT SUCCESS OF UNIVERSITY STUDENTS - Avhustiuk, Maria (Волинський національний університет імені Лесі Українки, 2020)
Purpose. The paper is focused on the theoretical analysis of some theoretical and methodological aspects of the relationship between metacognitive monitoring accuracy and learning achievement success of university students. In particular, we highlight some approaches to the relation between metacognitive monitoring accuracy and learning achievement success that is a quite common problem in the university learning activity. Methods. The theoretical and comparative methods of studying metacognitive monitoring accuracy and learning achievement success of university students have been used in the study. The necessity in studying some theoretical and methodological aspects of the notion has been caused by the impact of metacognitive monitoring accuracy on students’ learning activities. Results. The study aimed at revealing the role of metacognitive monitoring in the university learning activity, studying the extent to which changes in monitoring cause changes in the nature of the students’ control over their own cognitive activities, specifying the nature of relationship between levels of confidence and students successes in learning, etc. A noteworthy finding is that students are generally overconfident in their self-assessments and this overconfidence effect is greatest for students of poorer abilities as they are doubly cursed: they lack knowledge of the material, and lack the awareness of the knowledge that they do and do not possess. The erroneous belief that information is understood when it is not is regarded as the illusion of knowing or overconfidence in knowing; the notion can be a significant obstacle to the effectiveness of the learning activities. Conclusions. The results of the analysis found in the study can play an important role in the process of understanding the relationship between metacognitive monitoring accuracy and learning achievement success of university students.
Keywords: metacognitive monitoring; accuracy; learning achievement success; confidence; students; 159.955; 159.953